Pengaruh Pembelajaran Berbasis Aplikasi Google Classroom dan Kesiapan Belajar terhadap Kemandirian Belajar Siswa Kelas IX SMP Al Asy’ari Geger Bangkalan - Karim, Sya’roni; Sucipto, Sucipto; Sarmi, Ni Nyoman (LP. Ma'arif Janggan Magetan, 2024)
Humanity today is in deep sadness over the outbreak of the Corona virus Disease (Covid-19). The Indonesian government implements a learning from home policy, namely online learning. This research is a type of quantitative research. The sampling technique uses purposive sampling technique. The sample in this study was SMP Al Asy'ari Geger Bangkalan. Data collection methods in this study were interviews, questionnaires and tests. The results of the questionnaire and documentation are analyzed through three stages, namely correlation test analysis techniques, coefficiency and determination tests and t tests. The purpose of this study was to determine the effect of using the Google Classroom application on student learning readiness and learning independence of Class IX students of SMP Al Asy'ari Geger Bangkalan. The results showed that there was a significant difference between learning using Google Classroom on student learning readiness and learning independence of Class IX students of Al Asy'ari Geger Bangkalan Junior High School known Sig. (2-tailed) value of 0.016 > 0.05 and in the control class was 0.011 > 0.05 so that it can be concluded that the data on student learning independence produced in the research subjects were normally distributed. The suggestion in this study is that teachers can use innovative learning media such as Google Classroom so as to increase student interest in learning readiness and student learning independence.